Impacts of a specific model of training on improvement of maximal oxygen uptake in football players - Radenovic, D.; Dobrac, R.; Petrovic, B.; Kukric, A.; Stojanovic, T. (FIS communications in Physical Education, Sport and Recreation, 2016)
It is well known that aerobic power is very important, if not the most important functional parameter in modern football. Aerobic power is the parameter or property that we call maximum oxygen uptake. Training sessions for the improvement of maximum oxygen uptake require a well-planned program based on scientific facts and methods. In a sample of 17 football players from football club "Borac" Banja Luka it was investigated the possibility of improvement of maximum oxygen uptake, using the specific training model in duration of 4 weeks. To estimate maximal oxygen uptake was used beep-test. Value of the results obtained in the initial and final measurements were analyzed using t-test for paired samples (p=.0.05). Based on data obtained by the analysis it was concluded that the specific training model proved to be effective in improving maximal oxygen uptake.